การศึกษาลักษณะของฝ่ายบริการการพยาบาลที่เป็นเลิศในโรงพยาบาลระดับตติยภูมิ ปี พ.ศ. 2555 - เกศรา อัญชันบุตร (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
The purpose of this research was to study excellent nursing service department characteristics in tertiary hospitals at 2012. An Ethnographic Delphi Future Research (EDFR) technique was applied. Twenty experts including 3 hospital administrators, 4 nursing administrators, 3 committee members from nursing organizations, 6 staff nurses and 4 nursing professors were participated in this study. The study instruments were: (1) an interview guide for asking the experts to describe the excellent nursing service department, and (2) a questionnaire developed from the interview contents to ask a prior panel of experts for confirming the previous opinion. Study data were analyzed by using median and inter-quartile range to summarize the characteristics of excellent nursing service department. The results revealed that the excellent nursing service department characteristics were classified into 4 categories: 1. Organization outlook, consisting of 4 subcategories: 1.1 Flexibly organizational structure 1.2 Strategic planning and possible goals 1.3 Warm and caring climate 1.4 Supporting a quality of working life 2. Nursing management, consisting of 4 subcategories: 2.1 Giving a power and authority to staff 2.2 Effective human resource management 2.3 Applying knowledge management to work 2.4 Equal materials and budgeting management if comparing with other organizations 3. Nursing service, consisting of 2 subcategories: 3.1 A variety of nursing care 3.2 Effective quality of care and continuous of quality improvement 4. Staff characteristics consisting of 2 subcategories: 4.1 Basic competency 4.2 Specific competency of a leader and staff